Prevalence of Multidrug-resistant and Carbapenemase-producing Klebsiella Pneumoniae and Pseudomonas Aeruginosa Isolates in Tertiary Care Hospital in Kathmandu, Nepal - Darnal, Rojina; Ansari, Mehraj; Rai, Ganesh; Rai, Kul Raj; Rai, Shiba Kumar (Nepal Medical College Journal, 2021)
Carbapenemases are the enzymes that catalyze β–lactam groups of antibiotics. The carbapenemase producers are resistant to β–lactam antibiotics and are usually multidrug-resistant bacteria challenging widely used therapeutics and treatment options. Therefore, the detection of carbapenemase activity among clinical isolates is of great therapeutic importance. We aimed to study the MDR and carbapenemase-producing Klebsiella pneumoniae and Pseudomonas aeruginosa isolated from various clinical samples at a tertiary care hospital in Nepal. A total of 3,579 clinical samples were collected from the patients visiting the Department of Microbiology, B&B Hospital, Gwarko, Lalitpur. The samples were processed to isolate K. pneumoniae and P. aeruginosa and then subjected to antibiotic susceptibility testing (AST) by the Kirby-Bauer disk diffusion method. Phenotypic detection of carbapenemase activity was performed in the imipenem-resistant isolates by the modified Hodge test (MHT). Of the total samples, 1,067 (29.8%) samples showed significant growth positivity, out of which 190 (17.3%) isolates were K. pneumoniae and 121 (11.3%) were P. aeruginosa. Multidrug resistance was seen in 70.5% of the K. pneumoniae isolates and 65.3% of the P. aeruginosa isolates. Carbapenemase production was confirmed in 11.9%, and 12.2% of the imipenem-resistant K. pneumoniae and P. aeruginosa isolates, respectively, by the MHT. This study determined the higher prevalence of MDR among K. pneumoniae and P. aeruginosa; however, carbapenemase production was relatively low.